A Realization Analysis Of Received Motor Vehicle Tax And Behavior Of Motor Vehicle Name In The Regional Income Agency Of Central Sulawesi Province - Andhy Saputra; Nurfitriana Nurfitriana (Fakultas Ekonomi Universitas Indonesia Timur, 2020)
ABSTRACK Analysis of Motorized Vehicle Tax Revenue and Fees for Transfer of Motorized Vehicles at the Revenue Agency Office of Central Sulawesi Province. The purpose of this study was to determine the Performance of Local Governments in implementing Motorized Vehicle Tax Collection and Transfer of Motor Vehicle Title Fees at the Central Sulawesi Provincial Revenue Agency Office. The main theory used in this study is Mahmudi's opinion which states that the effectiveness of local taxes shows the ability of local governments to collect local taxes in accordance with the targeted amount of local tax revenue. This type of research uses descriptive quantitative with data processing approach techniques and unstructured interviews on 7 informants who have competition in the field of regional tax management in the Central Sulawesi Regional Revenue Agency. The results showed that the performance of the Regional Government in carrying out the collection of Motorized Vehicle Tax and Transfer of Motor Vehicle Title Fee at the Regional Office of the Revenue of Central Sulawesi Province has been very good in terms of the level of Growth, Effectiveness, and Contribution of Motorized Vehicle Tax and Motorized Vehicle Transfer Fee Duty towards revenue Local tax.